Prediksi Tingkat Timbulan Sampah 5 Tahun Mendatang (2023-2027) di TPA Ganet Kota Tanjungpinang - Veronika Amelia Simbolon; Tarisa; Hevi Horiza (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2023)
An increase in population growth affects an increase in waste generation, this has an impact on the provision of TPS, TPA, cleaning staff, transportation facilities and infrastructure, and also the operational budget. Predicting the level of waste generation is very important because the results of the predictions can be used to take proactive actions to solve waste problems in the future by the authorities. Therefore this study aimed to predict the waste generation that will affect the number of waste carriers in the next 5 years. The type of this research used descriptive quantitative. The data collection methods in this study by observation, study of documents, and study of literature. The results show that the prediction of the population of Tanjungpinang City in the next 5 years will increase where in 2027 the population is predicted to be 274,883 people and the amount of waste generation will decrease to 29,283 tons/year. This study concludes that the population has increased, waste generation has decreased in the next 5 years and there are no additional transportation facilities. The community is expected to be proactive about the policies carried out by the government and the Ganet TPA management by complying with existing regulations and disposing of waste in its place.